PENGARUH CR, DER, ROA, DAN PER TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI DI BEI - Lestari, Indah Sulistya Dwi; Suryantini, Ni Putu Santi (E-Jurnal Manajemen; Vol 8 No 3 (2019)DO - 10.24843/EJMUNUD.2019.v08.i03.p24, 2019)
This study aims to see stock price stability at a Pharmacy company listed on the Indonesia Stock Exchange (IDX) for the period 2014 - 2016 by using several variables such as Current Ratio, Debt to Equity Ratio, Return on Assets and Price Earning Ratio. This research is a type of quantitative research which used fundamental analysist by referring to an analysis of company performance that is used to predict stock prices in the future. The method of determining the sample in this study is based on purposive sampling technique that is in accordance with the criteria of eight pharmacy companies. The data used in this study were collected through non-participant observation methods using the data contained in the IDX. Testing of the hypothesis in this study using multiple linear regression analysis. The test results show that there is no significant influence on stock prices when using Current Ratio, Debt to Equity Ratio, Return on Assets and Price Earning Ration. On the contrary, Price Earning Ration partially has a positive and significant effect on the stock price of pharmaceutical companies in the 2014-2016 period. Keywords : fundamental analysis, current ratio , debt to equity ratio , r eturn on a sset, price earning ratio , stock price